Memorias sobre la mesa (2017)
This monograph is a creative exercise which it is a collection of chronicles about Sopo, town in which I grew. These chronicles tell histories about a reduced group of inhabitants of the town, much of them my family, among which stand out Victor Manuel Rojas Tellez, the painter.